Diet-Dependent Changes of the DNA Methylome Using a Göttingen Minipig Model for Obesity - Feng, Y.; Cirera, S.; Taşöz, E.; Liu, Y.; Olsen, L. H.; Christoffersen, B. Ø.; Pedersen, H. D.; Ludvigsen, T. P.; Kirk, R. K.; Schumacher-Petersen, C.; Deng, Y.; Fredholm, M.; et al. (Frontiers in Genetics, 2021)
Objective: Environmental factors can influence obesity by epigenetic mechanisms. The aim of this study was to investigate obesity-related epigenetic changes and the potential for reversal of these changes in the liver of Göttingen minipigs subjected to diet interventions. Methods: High-throughput liquid hybridization capture-based bisulfite sequencing (LHC-BS) was used to quantify the methylation status of gene promotor regions in liver tissue in three groups of male castrated Göttingen minipigs: a standard chow group (SD, N = 7); a group fed high fat/fructose/cholesterol diet (FFC, N = 10) and a group fed high fat/fructose/cholesterol diet during 7 months and reversed to standard diet for 6 months (FFC/SD, N = 12). Expression profiling by qPCR of selected metabolically relevant genes was performed in liver tissue from all pigs. Results: The pigs in the FFC diet group became morbidly obese. The FFC/SD diet did not result in a complete reversal of the body weight to the same weight as in the SD group, but it resulted in reversal of all lipid related metabolic parameters. Here we identified widespread differences in the patterning of cytosine methylation of promoters between the different feeding groups. By combining detection of differentially methylated genes with a rank-based hypergeometric overlap algorithm, we identified 160 genes showing differential methylation in corresponding promoter regions in the FFC diet group when comparing with both the SD and FFC/SD groups. As expected, this differential methylation under FFC diet intervention induced de-regulation of several metabolically-related genes involved in lipid/cholesterol metabolism, inflammatory response and fibrosis generation. Moreover, five genes, of which one is a fibrosis-related gene (MMP9), were still perturbed after diet reversion. Conclusion: Our findings highlight the potential of exploring diet-epigenome interactions for treatment of obesity.